As tramas do cinema de Peter Greenaway: processos de criação em The Tulse Luper Suitcases - Bonini, Eduardo Cunha (2010)
The purpose of this research is to study the creative processes manipulated by filmmaker Peter Greenaway in the construction of the project The Tulse Luper Suitcases. In this, one can find, in a full relational dialogue, movies, sites, live cinema performances, exhibitions, on line games, books, etc, posing as a complete potential system, a work in progress, whose limits between Medias that forge it are diluted. Our main goal is to understand how the project is structured and organized in a way that has made possible building a cross-media work closer to contemporary expressive forms. In this end, we have utilized the author s interviews and texts, from which we have removed the clues of his creative process. In order to achieve this goal, we have sought theoretical and methodological support in the theory of critical processes proposed by Cecilia Salles, which understands the creation process as a network construction. We have also established a dialogue on these arguments with some film expertises (DELEUZE, DUBBOIS, AUMONT, XAVIER), digital-medias theorists (MANOVICH, MACHADO) as well as some reviewers that have analyzed the work of this filmmaker. The concepts of encyclopedia and database-aesthetics, the later as it was proposed by Lev Manovich, have been used as drivers for the reflections over Peter Greenaway s creative procedures